KOMPOSISI NUTRISI PAKAN AYAM RAS PEDAGING MASA AKHIR (BROILER FINISHER) DARI BEBERAPA BAHAN PAKAN LOKAL - Nasruddin Nasruddin (Balai Riset dan Standardisasi Industri Palembang, 2010)
This research aims to study the nutritional content of chicken feed is sourced from local feedstuffs, Local feed ingredients used in this study are wheat bran, rice bran, tofu waste, fish meal, shellfish flour, cornstarch and salt. Feed ingredient is formulated in accordance with nutrient adequacy ratio, then from some formula steamed, rolled with a rolling pin and dried fish. Pellet feed testing including moisture content, protein content, fat content, ash content, calcium content, and phosphorus levels. Tests on the feed from several treatment SNI 01-3931-2006 using method of feeding broiler final period (broiler finisher). Results of laboratory testing of food to feed formula B with 25 g of wheat bran, rice bran 19 g, 12 g flour tofu waste, fish meal 17 g, 5 g shellfish flour, corn flour 20 g, 2 g salt and water content of 7,640% yield, 22,850% of protein, fat 6,114%, 6,320% ash, calcium 0,914% and 0,817% phosphorus. For these parameters meet the requirements of SNI 01-3931-2006 broiler feed the final period (Broiler finisher).